2010
DOI: 10.1097/bpo.0b013e3181df619d
|View full text |Cite
|
Sign up to set email alerts
|

Is Percutaneous Adductor Tenotomy as Effective and Safe as the Open Procedure?

Abstract: Level II therapeutic study-prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
17
0
4
Order By: Relevance
“…Anatomical findings from this study are generally consistent with previous research. For example, dissection and surgical studies have also reported the proximal attachment of AL to be typically tendinous on its superficial surface in 90 to 100% of specimens (Tuite et al,1998; Strauss et al,2007; El Hage et al,2010). Secondary superior projections from AL to the distal rectus sheath, pubic symphysis, contralateral AL tendon, and ilio‐inguinal ligament concur with detailed early anatomical descriptions (Eisler,1912; Testut and Latarjet,1948) and more recent experimentally based investigations (Gibbon,1999; Robinson et al,2007; Davis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical findings from this study are generally consistent with previous research. For example, dissection and surgical studies have also reported the proximal attachment of AL to be typically tendinous on its superficial surface in 90 to 100% of specimens (Tuite et al,1998; Strauss et al,2007; El Hage et al,2010). Secondary superior projections from AL to the distal rectus sheath, pubic symphysis, contralateral AL tendon, and ilio‐inguinal ligament concur with detailed early anatomical descriptions (Eisler,1912; Testut and Latarjet,1948) and more recent experimentally based investigations (Gibbon,1999; Robinson et al,2007; Davis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the advent of percutaneous techniques, shorter procedural times and improved aesthetic outcomes became possible. Furthermore, there is evidence to suggest that percutaneous tenotomy is as safe and effective as the open procedure.It is notable that the extent of the tendinous portion divided in the muscle of interest appears directly correlated with increased postoperative mobility [54,55] . In animal studies, ultrasoundguided percutaneous tenotomy has been shown to increase complete tendon transection and decrease damage to surrounding structures compared to palpation-guided tenotomy (63).…”
Section: Percutaneous Tenotomymentioning
confidence: 97%
“…A brief listing of clinical indications and contraindications for percutaneous tenotomy are listed in Table 5. A comprehensive discussion of this topic is beyond the scope of this review [53][54][55][56][57][58][59][60][61][62][63] . Percutaneous tenotomy is ideally performed at the bedside or in an outpatient setting.…”
Section: Percutaneous Tenotomymentioning
confidence: 99%
“…El Hage et al 53 , in Beirut, performed a prospective comparative study of twenty-seven patients (fifty hips) to determine if percutaneous adductor tenotomy was as safe and effective as an open tenotomy. In this unique study, a pediatric orthopaedic surgeon first performed a percutaneous adductor tenotomy, with a second surgeon then extending the wound to explore the percutaneous adductor tenotomy and to complete the tenotomy, if needed.…”
Section: Neuromuscular Diseasementioning
confidence: 99%